Microplastics separation and subsequent carbonization: Synthesis, characterization, and catalytic performance of iron/carbon nanocomposite. (1st January 2022) - Wang, Chongqing; Huang, Rong; Sun, Ruirui; Yang, Jiapeng; Dionysiou, Dionysios D.
Abstract: Microplastics (MPs), as emerging contaminants, have gained increasing global attention due to their wide distribution and serious threats. Physical techniques are effective for separating MPs from water environment such as in wastewater treatment plants, but the disposal of the separated MPs becomes an emerging problem. A novel strategy of MPs separation and subsequent sustainable disposal is proposed. MPs separation was effectively obtained via iron coagulation. Conversion of the coagulated material into carbon material was conducted by facile carbonization. The formation of magnetic carbon/iron nanocomposite was verified by various characterization methods. Carbon/iron nanocomposite obtained at 800 °C (MPC800) was used as heterogeneous catalyst for evaluating the degradation of a toxic Rhodamine B (RhB). The effects of H2 O2, pH, and temperature on degradation performance were studied associated with RhB removal efficiency and kinetic analysis. Under proper conditions, RhB removal of 97.57% was obtained at 20 min. The activation energy of RhB degradation is 46 kJ/mol, lower than that of previous reports. Quenching tests and electron spin resonance spectra verified the dominant role of OH radical in RhB degradation. Conversion of MPs into effective catalyst for wastewater treatment offers a sustainable strategy for MPs disposal, guided by the "waste treating waste" concept. Graphical abstract: Pollutant degradation using carbon nanocomposite derived from coagulated microplastics guided by the "waste treating waste" concept. Image 1 Highlights: Facile removal of microplastics was obtained by iron coagulation. Carbon/iron nanocomposites (CINC) were formed by carbonization of coagulated microplastics. CINC/H2 O2 system displays high catalytic performance for pollutant degradation. This study offers a novel strategy for microplastics removal and their sustainable reuse.